Intrigue and Darkness: Contrasting Treatments of a Constellation. Schiller’s The Visionary and Hoffmann’s The Sandman - Salmerón Infante, Miguel (Escritura e Imagen, 2025)
This article compares two stories Der Geisterseher (The Ghost Seer) by Schiller (1787-1798) and Der Sandmann (The Sandman) by E.T.A. Hoffmann from 1871. Both texts have in common the presence of the dark and the conspiratorial. However, the approach to that feeling and this intrigue are very different in both cases. Schiller strives to make us see that the magical and the unknown are nothing more than elements that conspirators use to manipulate their victim. Hoffmann, for his part, leaves in suspense the question of whether the protagonist is the object of persecution by his attackers or if everything is the result of his feverish and pathological imagination. Schiller, claiming the lights of reason against the darkness, indirectly alludes to the religious-political struggle that was ongoing in his time in the Duchy of Württemberg. In contrast to Schiller’s denigration of the mysterious, Hoffmann attributes to this dimension an effective impact on the human spirit and the possibility of opening a door to that of which we are not aware. In fact, Sigmund Freud’s essay Das Unheimliche (The Uncanny), dating from 1919, takes Hoffmann’s story as its central reference.